Loss of SMYD1 Results in Perinatal Lethality via Selective Defects within Myotonic Muscle Descendants - Tara L. Rasmussen; Haley O. Tucker (Diseases, 2018)
SET and MYND Domain 1 (SMYD1) is a cardiac and skeletal muscle-specific, histone methyl transferase that is critical for both embryonic and adult heart development and function in both mice and men. We report here that skeletal muscle-specific, myogenin (myoG)-Cre-mediated conditional knockout (CKO) of Smyd1 results in perinatal death. As early as embryonic day 12.5, Smyd1 CKOs exhibit multiple skeletal muscle defects in proliferation, morphology, and gene expression. However, all myotonic descendants are not afflicted equally. Trunk muscles are virtually ablated with excessive accumulation of brown adipose tissue (BAT), forelimb muscles are disorganized and improperly differentiated, but other muscles, such as the masseter, are normal. While expression of major myogenic regulators went unscathed, adaptive and innate immune transcription factors critical for BAT development/physiology were downregulated. Whereas classical mitochondrial BAT accumulation went unscathed following loss of SMYD1, key transcription factors, including PRDM16, UCP-1, and CIDE-a that control skeletal muscle vs. adipose fate, were downregulated. Finally, in rare adults that survive perinatal lethality, SMYD1 controls specification of some, but not all, skeletal muscle fiber-types.